Karakter Religius Siswa setelah Mengikuti Kegiatan Shalat Berjama’ah di Sekolah - Ami, Mucharommah Sartika; Anggraini, Feni (Universitas KH. A. Wahab Hasbullah, 2024)
This research aims to describe the religious character that students have after participating in congregational prayer activities at school. This research was conducted at SMP Darul Ulum Kepuhdoko involving 30 randomly selected students in grades VII, VIII, and IX. The method used is a qualitative survey using a closed questionnaire instrument with four options: always, often, rarely, and never. The collected data was analyzed descriptively. The research results showed that students’ religious character was in the high category (83%). The majority of male and female students have high religious character, only a small number have moderate religious character, and none have low religious character. This shows that congregational prayer activities have a positive influence on improving the religious character of students at SMP Darul Ulum Kepuhdoko.